Vapor transport deposited tin monosulfide for thin-film solar cells: effect of deposition temperature and duration. Issue 12 (8th March 2019) - Lee, Dajeong; Cho, Jae Yu; Yun, Hee-Sun; Lee, Doh-Kwon; Kim, Taehoon; Bang, Kijoon; Lee, Yun Seog; Kim, Ho-Young; Heo, Jaeyeong
Abstract : Proper control of the morphology and preferred orientation of the SnS absorber is crucial for increasing the open-circuit voltage of thin-film solar cells. Abstract : The influence of the vapor transport deposition (VTD) conditions of tin sulfide (SnS) on the formation of secondary phases, preferred orientation, and solar cell performance is investigated in this study. It is concluded that 600 °C is the optimal growth temperature for the formation of pure SnS absorbers. When the growth temperature was 550 °C, the formation of secondary Sn2 S3 and SnS2 phases was detected by Raman analysis. When the growth temperature was 625 °C, a noticeable change in morphology was observed with the plate-shaped grains aligned vertically to the substrate, which is detrimental to solar cell performance. The duration of growth also affected the morphology of the SnS absorber. Thin absorbers exhibited strong (120) preferred orientation. With increased duration of growth, (101) and (111) orientations increased. Such a variation in preferred orientation influenced the SnS/CdS solar cell's performance. When the absorber thickness was as thin as ∼0.7 μm, the cell was prone to shunting and severe series resistance. When the absorber was as thick as ∼3.0 μm, physical shunting prevailed, worsening the performance of the cell. The highest efficiency of 3.93% with good cell-to-cell uniformity was achieved when the absorber thickness was ∼1.2 μm. The good stability of the best device was also confirmed under continuous illumination and damp-heat conditions for 100 h.